Seeding legal options - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Seeding Solutions: Volume 2 Options for national laws governing access to and control over genetic resources The Crucible II Group, Co-publication by the International Development Research Centre, the Dag Hammerskjöld Foundation and the International